Anti-Dumping Committee’s Strategy to Confront Dumping Practices: Indonesian Law and International Law Perspective - Rifda Ayu Akmaliya; Satria Unggul Wicaksana Prakasa; Sonny Zulhuda (Journal of Private and Commercial Law, 2023)
This study investigates the Indonesian Anti-Dumping Committee's role and legal efforts in addressing dumping practices within the context of Indonesia's membership in the World Trade Organization (WTO) and adherence to the General Agreement on Tariffs and Trade (GATT). Previous research has demonstrated the existence of dumping in imported polyester staple fiber products, leading to the committee's proposal of anti-dumping duties. The committee is responsible for receiving reports on alleged dumping and producing final reports. Despite these efforts, the study reveals an ongoing increase in dumping cases, causing significant social, psychological, and economic consequences for the country. The current institution dealing with dumping practices is considered inefficient and ineffective. To gain a comprehensive understanding of the issue, the research employs a sociolegal research method with a disciplinary approach, acknowledging that relying solely on normative law is insufficient to address dumping practices. In conclusion, this study aims to shed light on the Indonesian Anti-Dumping Committee's role and its legal framework in countering dumping practices. The rising dumping cases and the perceived inefficiency of the existing institution are worrisome. By utilizing a sociolegal research method with a disciplinary approach, the study strives to offer a holistic understanding and potentially contribute to more effective solutions in combating dumping practices.